Implementasi Forecasting Penjualan Obat Menggunakan Metode Straight Line Model Pada Apotek Ficus Bengkulu - Puspita, Nara; Kanedi, Indra; Beti, Ila Yati (Jurnal Media Infotama, 2023)
Abstract: Forecasting is an analytical technique that uses historical data as input to make informed forecasts to determine the direction of future trends. Forecasting can be used for business actors to be able to manage and organize sales strategies and inventory in the following month or year. Ficus Bengkulu Pharmacy is one of the pharmacies in the city of Bengkulu which sells various types of medicines, both prescription and non-prescription. The processing of drug sales data is still conventional, so when pharmacists want to know drug sales and drug supplies they have to look at the records from the book so it takes a very long time. Therefore, an inventory application is needed that is able to record drug records and provide recommendations in the form of forecasting to maintain and control drug use and drug demand which is carried out every month. The forecasting method used is the Straight Line Model Method. Based on the implementation of Tremenza drug sales data for 2021, the results for forecasting Tremenza drug sales in 2022 are obtained every month from January to December 2022, where the average value of sales forecasting results per month is 1041 and an increase of 4.83% from average sales per month in the previous year.